REPRESENTASI UNSUR KLENIK DI DALAM FILM "KAFIR"(ANALISIS SEMIOTIKA ROLAND BARTHES) - Muhammad Andhika Pramudhia (2022)
This research is a study using a semiotic method on a horror movie entitled "Kafir". This research aims to perceive the significance of occult elements in every specific scene in the movie. In addition to that, this research will examine 3 aspects of the semiotic method which are the denotation aspect, connotation aspect, and myth aspects. The denotation aspect is an immediate meaning of the scenes, whereas the connotation aspect is an implication that is formed in community groups and tends to be subjective. On the other hand, myth aspects is a meaning that is formed in community groups and has closely related to mystical and horror aspects. Kafir, as a movie, will be analyzed using the semiotic method analysis by Roland Barthes. This research will be analyzed using descriptive qualitative methodology with the semiotic analysis from Roland Barthes that is based on communications concept and occult theory from experts that researchers gained from textbooks, scientific journals, and other scientific literature to examine the 3 aspects of the semiotic method in denotation, connotation and myths aspects from every message that is delivered. The result of this research shows that the symbols of the occult in "Kafir" film are being represented through different gestures and objects. Denotation meaning is an immediate meaning of the scenes, and the denotation meaning in the movie shows that several people are affected by witchcraft due to occults rituals sent by other people. Connotation meaning is a symbol which was a result of researcher interpretation, and in this movie shows that there is a physical and spiritual impact due to occults rituals carried out by other people through the intermediary of objects related to the recipient. Myths are things that exist and develop in a society by associating something that is seen in real with an implied sign. Myths in infidel films show witchcraft as an occult ritual that connects the sender and recipient through certain objects related to the beliefs of the surrounding community. Suggestions that researchers can give for further research, Researchers hope that there will be research on the representation of mystical elements of other cultures in a film such as the mystical culture of Sumatra, the mystical culture of Bali, Kalimantan, and others. Keyword: Representation, Culture, Occult, Horror Film, Roland Barthes